(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. Libertà di culto e pandemia - 3. Logica deontica e bilancia costituzionale - 4. Le critiche agli interventi governativi - 5. Logica giuscostituzionale - 6. Libertas ecclesiae e pandemia - 7. Conclusioni e prospettive. Constitution and Religion in Italy in a Time of Pandemic ABSTRACT: In the first half of 2020, in Italy the coronavirus (Covid-19) has spread quickly, putting the country in an unprecedented emergency. From here stemmed the Government’s measures, which were (and are) without parallel in the history of the Italian State. These measures have led to an animated debate, especially when associated to the limitations imposed on the public liturgical life of the Catholic Church. That was also incorporated into the discussion concerning the long-standing principle-method of bilateralism, as established in Articles 7.2 and 8.3 of the Italian Constitution. With this article the Author analyses this debate in the light of the constitutional duty to protect human health, in the individual and collective sense of the terms.